Querida Promotora - Faiver-Serna, Cristina (ACME, 2024)
This open letter to the promotoras de salud (community health workers) of Long Beach, California explores the multifaceted demands placed on low-wage, highly skilled health educators within the nonprofit industrial complex, and exposes the geographies of Latinx health precarity from the perspective of urban health care feminized labor. The letter also shares and celebrates the deep commitment to justice that promotoras struggle toward through their care work.